The effect of measurement method on static weight distribution to all legs in dogs using the Quadruped Biofeedback System - Phelps, H. A.; Ramos, V.; Shires, P. K.; Werre, S. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
An application to measure static quadruped load distribution would be highly beneficial in the assessment of rehabilitation and lameness in many small animal patients. The scope of this study was to analyze the effects of confinement, location and local environment on the measurement of static quadruped load distribution as measured by the Quadruped Biofeedback System in normal dogs in order to better prescribe the use of this system. A prospective study of 20 healthy adult dogs was performed to evaluate effects on measurement on quadruped load distribution. Data collection in the form of mean load per extremity was recorded four times in five positions for a total of 20 measurements for each limb. A replicated cross-over design in which a mixed effect, repeated measures analysis of variance was used to test for main effects of treatment and end as well as their interaction. The effects of right vs. left within each end and for each end was analyzed for each treatment and significance of p<0.01 was established. Measurements were taken from 20 healthy adult dogs with no obvious lameness at the time of data collection. Analysis by end suggests that measurements were affected in similar manners in comparable locations. Each method demonstrated consistency in measurement without any significant influence by day or session, suggesting that one standardized method be established for measurement. With standardization, the Quadruped Biofeedback System has potential use as a reliable instrument for the measurement of quadruped load distribution in dogs.
Keywords: Rehabilitation therapy; lameness; force plate analysis; Quadruped Biofeedback System